Claritas scripturae in Luther: perspectives for the preaching! - Stange, Klaus Andreas (Vox Scripturae - Revista Teológica Internacional, 2016)
The Pentecostal movement and his speech promise freedom, but enslave; provide and promote material prosperity, but alienate; announce healings and miracles that God will operate, but only arouse the need for consumption; They speak of the Gospel, but it’s a legalistic discourse; witness of a triune God, but that is nothing more than selflove. In a post-modern context, where neo-Pentecostal churches take and incorporate a postmodern identity, what is the meaning and significance to review the Lutheran principle of claritas scripturae? Is it possible that, in the advent of the 500th anniversary of the Reformation, the scriptural principle of Luther still has something to say and contribute to the performance of contemporary preaching? Our thesis is that a reaffirmation of the scriptural principle Luther’s into a postmodern context, into the South American context with social and religious contrasts of the most diverse and placed in dialogue with the discourse of neo-Pentecostal churches, contribute to liberating preaching, evangelical, graceful, distinguishing law and gospel.